1998
DOI: 10.1093/tropej/44.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Brief report. Breastfeeding practices in urban Riyadh

Abstract: Three hundred and forty-seven mother-infant pairs attending a well baby clinic in a University Hospital in Riyadh were interviewed on the type of feeding given to their infants. The objective was to assess the latest trend of infant feeding practices in an urban population and to compare present trends and their significance with previous reports. Results showed that 32.4 per cent of infants at 3 months and 22.1 per cent of infants at 6 months were exclusively breastfed; 18.2, 48.4, and 65.4 per cent were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 0 publications
0
24
1
1
Order By: Relevance
“…Results from three other studies reported that education has no significant effect on breastfeeding status and duration [23,32,33]. However, sample sizes in these three studies were very small (see Table 2), and thus, their results might be underpowered.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Results from three other studies reported that education has no significant effect on breastfeeding status and duration [23,32,33]. However, sample sizes in these three studies were very small (see Table 2), and thus, their results might be underpowered.…”
Section: Resultsmentioning
confidence: 93%
“…Four studies concluded that working mothers breastfed less frequently and had shorter duration than non-workers, and that these differences were statistically significant [21,26,28,32]. A further five studies found that working status had no significant effect on breastfeeding practices and duration [23,24,30,31,33], and one study reported a higher ‘exclusive breastfeeding’ rate among working mothers compared to non-working mothers ( p  = 0.005) [22].…”
Section: Resultsmentioning
confidence: 99%
“…6 In Saudi Arabia there has been a considerable change in the pattern of breastfeeding in recent decades due to population transition as a result of advancements in socioeconomic status. 7 Breastfeeding in Saudi Arabia has been customary; 8 its duration used to exceed the age of 24 months, and solid food would be introduced as late as 12-18 months and complementary to breastfeeding. 9 Studies from Saudi Arabia have recorded a progressive decline in breastfeeding practice and duration, especially among young mothers in urban areas, [10][11][12] with early introduction of bottle feeding 12,13 and earlier introduction of solid foods.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous survey on a similar group of mothers, 97% planned to breast-feed when they were pregnant. 1 In our study, the 11 mothers (6%) who did not breast-feed during their stay in the hospital had a shorter average stay in the hospital than those who breast-fed their infants (30±10 and 55±37 hours, respectively, P=<0.0001), and therefore, may not have had the chance to start breast-feeding. This is supported by the fact that breast-feeding was delayed (16±9 hours) in the group of infants in this study.…”
Section: Discussionmentioning
confidence: 52%